2019
DOI: 10.4274/tjo.galenos.2019.32748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pupillary Light Reflex in Amblyopic Eyes Using Dynamic Pupillometry

Abstract: Objectives: To evaluate the pupillary light reflex responses in patients with unilateral strabismic and anisometropic amblyopia using dynamic pupillometry. Materials and Methods: A total of 102 eyes of 51 patients with unilateral amblyopia were included in this cross-sectional study. Of the 51 patients, 37 (72.5%) had strabismic amblyopia and 14 (27.5%) had anisometropic amblyopia. All patients underwent complete ophthalmological examination, and pupillary light reflex responses were measured using a computeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, it is known that amblyopic eyes may have a fairly small RAPD (≤0.6 logMAR units), which makes it difficult to distinguish (9,20). A recent study conducted by Bitirgen et al (27) investigated the dynamic pupillary responses of patients with anisometropic amblyopia and reported that these eyes had a shorter contraction duration when compared with the fellow eyes. They stated that the shorter contraction time may not only facilitate early diagnosis of amblyopia, but may also be useful to help explain mechanisms involved in amblyopia pathophysiology (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known that amblyopic eyes may have a fairly small RAPD (≤0.6 logMAR units), which makes it difficult to distinguish (9,20). A recent study conducted by Bitirgen et al (27) investigated the dynamic pupillary responses of patients with anisometropic amblyopia and reported that these eyes had a shorter contraction duration when compared with the fellow eyes. They stated that the shorter contraction time may not only facilitate early diagnosis of amblyopia, but may also be useful to help explain mechanisms involved in amblyopia pathophysiology (27).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by Bitirgen et al (27) investigated the dynamic pupillary responses of patients with anisometropic amblyopia and reported that these eyes had a shorter contraction duration when compared with the fellow eyes. They stated that the shorter contraction time may not only facilitate early diagnosis of amblyopia, but may also be useful to help explain mechanisms involved in amblyopia pathophysiology (27). Kase et al (28) found no significant alteration in the amplitude or maximum velocity of the contraction in amblyopic and normal eyes using an infrared electropupillogram.…”
Section: Discussionmentioning
confidence: 99%
“…One of less noticed in this regard is changes in pupillary dynamic responses while providing different stimuli. Limited studies have provided these characteristics in different eye conditions including amblyopic patients, ( 14 ) people with multiple sclerosis, ( 15 ) people with diabetic retinopathy, ( 16 ) people with retinitis pigmentosa, ( 17 ) and finally while reducing or increasing accommodation ( 10 ). However, a review of available studies shows that evaluation of dynamic pupil changes after near ocular work has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to point out that the laboratory environment always remained in the same conditions: ambient lighting lamps were turned off and in complete silence, since studies analyzing multiple sclerosis and recognition of amblyopic eye advise taking these variables into account [21][22][23].…”
mentioning
confidence: 99%